Activation Mechanism of Fe2+ in Pyrrhotite Flotation: Microflotation and DFT Calculations - Qiang Song; Xiong Tong; Pulin Dai; Xian Xie; Ruiqi Xie; Peiqiang Fan; Yuanlin Ma; Hang Chen (Molecules, 2024)
In industrial manufacturing, pyrrhotite(Fe1−xS), once depressed, is commonly activated for flotation. However, the replacement of CuSO4 is necessary due to the need for exact control over the dosage during the activation of pyrrhotite, which can pose challenges in industrial settings. This research introduces the use of FeSO4 for the first time to efficiently activate pyrrhotite. The impact of two different activators on pyrrhotite was examined through microflotation experiments and density functional theory (DFT) calculations. Microflotation experiments confirmed that as the CuSO4 dosage increased from 0 to 8 × 10−4 mol/L, the recovery of pyrrhotite initially increased slightly from 71.27% to 87.65% but then sharply decreased to 16.47%. Conversely, when the FeSO4 dosage was increased from 0 to 8 × 10−4 mol/L, pyrrhotite’s recovery rose from 71.27% to 82.37%. These results indicate a higher sensitivity of CuSO4 to dosage variations, suggesting that minor alterations in dosage can significantly impact its efficacy under certain experimental conditions. In contrast, FeSO4 might demonstrate reduced sensitivity to changes in dosage, leading to more consistent performance. Fe ions can chemically adsorb onto the surface of pyrrhotite (001), creating a stable chemical bond, thereby markedly activating pyrrhotite. The addition of butyl xanthate (BX), coupled with the action of Fe2+ on activated pyrrhotite, results in the formation of four Fe-S bonds on Fe2+. The proximity of their atomic distances contributes to the development of a stable double-chelate structure. The S 3p orbital on BX hybridizes with the Fe 3d orbital on pyrrhotite, but the hybrid effect of Fe2+ activation is stronger than that of nonactivation. In addition, the Fe-S bond formed by the addition of activated Fe2+ has a higher Mulliken population, more charge overlap, and stronger covalent bonds. Therefore, Fe2+ is an excellent, efficient, and stable pyrrhotite activator.